Myo-Inositol and Its Derivatives: Their Emerging Role in the Treatment of Human Diseases - Chhetri, Dhani Raj (Frontiers in Pharmacology, 2019)
Myo inositol has been established as an important growth promoting factor of mammalian cells and animals. The role of myo-inositol as a lipotropic factor has been proven in addition to its involvement as co-factors of enzymes and as messenger molecules in signal transduction. Myo-inositol deficiency leads to intestinal lipodystrophy in animals and ‘inositol-less-death’ in some fungi. Of late, diverse uses of myo-inositol and its derivatives have been found in medicinal research. These compounds are used in a variety of ailments starting from diabetes to cancer and continued research in this direction promises a new future in therapeutics. In different diseases, inositols implement different strategies for therapeutic actions like tissue specific increase or decrease in inositol products, production of IPGs, conversion of MI to DCI, modulation of signal transduction, regulation of ROS production etc. Though inositol pharmacology is a relatively lesser known field still recent years have generated a critical mass of information on the subject. This review aims to summarize our current understanding on the role of inositol derivatives in ameliorating the symptoms of different diseases.